Convolvulus plant—A comprehensive review from phytochemical composition to pharmacy. (11th November 2019) - Salehi, Bahare; Krochmal‐Marczak, Barbara; Skiba, Dominika; Patra, Jayanta Kumar; Das, Swagat Kumar; Das, Gitishree; Popović‐Djordjević, Jelena B.; Kostić, Aleksandar Ž.; Anil Kumar, Nanjangud V.; Tripathi, Ayushi; Al‐Snafi, Ali Esmail; Arserim‐Uçar, Dılhun Keriman; et al.
Abstract : Convolvulus genus is a representative of the family of Convolvulaceae. Convolvulus plants are broadly distributed all over the world and has been used for many centuries as herbal medicine. Convolvulus genus contains various phytochemicals such as flavonoids, alkaloids, carbohydrates, phenolic compounds, mucilage, unsaturated sterols or terpenes, resin, tannins, lactones, and proteins. This review highlights the phytochemical composition, antimicrobial and antioxidant activities, application as food preservative, traditional medicine use, anticancer activities, and clinical effectiveness in human of Convolvulus plants. All the parts of Convolvulus plants possess therapeutic benefits; preliminary pharmacological data validated their use in traditional medicine. However, further preclinical and clinical experiments are warranted before any application in human health.